Apakah Latar Belakang Pendidikan Mempengaruhi Pemahaman tentang Konsep Sains? : Studi Kasus Calon Guru Sekolah Dasar - Urmila Umardianti; Supartinah Supartinah; Wahyu Kurniawati (Postgraduate, University of Mataram, 2023)
This research is a quantitative study to determine the effect of educational background on the understanding of the science concept of UPY PGSD students. This research is based on the low understanding of the science concept as evidenced by the percentage of science learning test results, namely 67.6% of the total number of semester 2 PGSD UPY students scored below 80. The method used in this research is ex post facto quantitative which is used to determine the cause of the low understanding of students' science concepts in terms of their educational background. The data collection used an educational background questionnaire and a science concept understanding test that had been tested for validity and reliability. The research shows the results of the t-test namely tcount<ttable (0.095 < 0.931), then Ho is accepted and Ha is rejected, which means that there is no significant influence between students' educational background on the understanding of science concepts. However, there is a unidirectional relationship between the two with the result of a positive correlation test (r) of 0.055 and contributing an influence of 0.3% from the educational background on understanding the science concept of PGSD UPY students.